Desenvolvimento pós-embrionário de duas espécies de piolho-de-cobra (Diplopoda; Polydesmida; Pyrgodesmidae) do Pantanal mato-grossense - Gastaldi, Vinícius Daguano [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Development patterns can be useful for identification in Diplopoda, but they are rarely studied for Neotropical species. The present paper brings the identification of the developmental stadia of two Neotropical species, the parthenogenetic diplopod Poratia salvator Golovatch & Sierwald, 2000 and the bisexual species Myrmecodesmus hastatus Schubart, 1945. Both species occur in floodable areas in the Pantanal of Mato Grosso, Brazil. Poratia salvator presents seven developmental stadia; the adult (the last stadium) possesses 17 rings, of which 16 are podous, most of them with two pairs of legs. Only one apodous ring is present - the collum - which is present since the first developmental stadium. Myrmecodesmus hastatus presents eight developmental stadia; the adult (the last stadium) possesses 18 rings, of which 17 are podous, most of them with two pairs of legs. Only one apodous ring is present - the collum - that is present since the first developmental stadium. Both species present anamorphic post-embryonic development, of the teloanamorphic type, which means that new rings are added up to the last developmental stadium

Os padrões de desenvolvimento de diferentes espécies podem ser úteis para identificação em Diplopoda, mas estes raramente são estudados para espécies Neotropicais. Nesse sentido, este trabalho teve o objetivo de descrever os estádios de desenvolvimento do diplópodo partenogenético Poratia salvator Golovatch & Sierwald, 2000 e da espécie bissexual Myrmecodesmus hastatus Schubart, 1945. Ambas as espécies ocorrem em áreas alagáveis do Pantanal do Mato Grosso, Brasil. Poratia salvator apresenta sete estádios de desenvolvimento; o adulto (último estádio) possui 17 anéis corporais, sendo que 16 deles apresentam pares de pernas, em sua maioria com dois pares. Apenas um anel sem pernas está presente, o collum, o qual ocorre desde o primeiro estádio de desenvolvimento. Myrmecodesmus hastatus apresenta oito estádios de desenvolvimento; o adulto (último estádio) possui 18 anéis corporais, sendo que 17 desses apresentam pares de pernas, em sua maioria com dois pares. Nesta espécie também apenas um anel sem pernas está presente, o collum, o qual ocorre desde o primeiro estádio de desenvolvimento. Ambas as espécies apresentam desenvolvimento pós-embrionário anamórfico, do tipo teloanamórfico, o que significa que novos anéis corporais são adicionados até o último estádio de desenvolvimento
Keywords: Milípede; Anamorfose; Fisiologia veterinaria; Pantanal Mato-grossense (MS e MT)